Personal characteristics of MPs and legislative behavior in moral policymaking - Baumann, Markus; Debus, Marc; Müller, Jochen (Legislative studies quarterly, 2015)
Theoretical and empirical models of legislative decision making in parliamentary democracies typically neglect the policy preferences of individual MPs and instead focus on political parties and possible institutional constraints. We argue that MPs actually make judgments and decisions on the basis of their preferences, which are shaped by their personal characteristics. However, given the strength of parties in most parliamentary systems, the impact of personal characteristics on legislative behavior is rarely visible. Therefore, we examine a moral issue. Looking at cosponsorship, parliamentary speeches, and votes in the German Bundestag, we analyze the legislative procedure on the regulation of preimplantation genetic diagnosis (PGD) in Germany in 2011. We show that the legislative behavior of MPs does not only reflect partisan conflict but is also influenced by the preferences of the constituents and MPs’ own personal characteristics such as: religious denomination, gender, and parental status.